AN ANALYSIS OF POSITIVE POLITENESS STRATEGIES IN SPIDERMAN: FAR FROM HOME MOVIE(2019) - Indri Novita Sari; Anam Sutopo (STKIP Siliwangi, 2024)
Communication is an inevitable aspect of human life, driven by our social nature and the need to interact with others through language. Politeness plays a crucial role in communication across all cultures. In this research, the researchers explore the positive politeness strategies depicted in the movie Spiderman: Far From Home. The aim of this research is to identify the various positive politeness strategies used by the characters., pin down the most dominant strategy, and investigate the elements influencing their utilization of positive politeness as proposed by Brown and Levinson. This research employs a qualitative approach. Scrutinizing dialogue data derived from scenes demonstrating positive politeness. The findings elucidate eight positive politeness strategies used by the characters in the movie, with